Acute Change in Vascular Tone Alters Intima-Media Thickness - Thijssen, Dick H.J.; Scholten, Ralph R.; van den Munckhof, Inge C.L.; Benda, Nathalie; Green, Daniel J.; Hopman, Maria T.E. (Hypertension (Dallas, Tex. 1979), 2011)
Atherosclerosis is a lifelong process involving artery wall thickening. Increased wall thickness has been widely adopted as a preclinical surrogate marker of atherosclerosis. A prerequisite for such a surrogate marker is that it is a structural characteristic of the vessel wall that is not subject to acute changes. The purpose of this study was to examine the acute effects of vasodilator drug administration on wall thickness of the carotid and superficial femoral arteries. High-resolution ultrasound was used to examine carotid and femoral artery diameters and wall thickness in 15 young (25±4 years of age) and 15 older (70±6 years of age) healthy men who were administered sublingual glyceryl trinitrate. Diameter and wall thickness were collected before and across a 10-minute period after glyceryl trinitrate administration. Glyceryl trinitrate induced a significant increase in carotid and femoral artery diameter and a decrease in wall thickness in both young and older men (both P<0.001). The latter was significantly larger than in young men (both P<0.01). The changes in carotid artery wall thickness in both young (35±23 μm) and older men (71±46 μm) approximate those considered prognostically relevant. Collectively, our data suggest that vasodilator drug administration induces a rapid and marked decrease in wall thickness, which mirrors conduit artery vasodilation in both young and older men. This finding confirms the presence of acute changes in wall thickness and has important implications for future studies that assess artery wall characteristics as a surrogate measure of atherosclerosis.